The TEI Critical Apparatus Toolbox: Empowering Textual Scholars through Display, Control, and Comparison Features - Marjorie Burghart (Journal of the Text Encoding Initiative)
The various mechanisms offered by the TEI schema and Guidelines for the encoding of critical editions suffer from one major shortcoming: the lack of user-friendly tools allowing philologists and their readers to display and process TEI-encoded editions. After witnessing –and personally experiencing– this frustration, I decided to develop an application especially dedicated to supporting philologists in their work, and helping them to fully benefit from their encoding work. The TEI Critical Apparatus Toolbox is now available online (http://ciham-digital.huma-num.fr/teicat/). This article describes the context in which this application was developed, its current features, and the plans for future improvements.